2016
DOI: 10.17235/reed.2016.4521/2016
|View full text |Cite
|
Sign up to set email alerts
|

If you suffer from type-2 diabetes mellitus, your ERCP is likely to have a better outcome

Abstract: Editorial dealing with the protective action on biliary sphincterotomy complications given by type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
0
1
Order By: Relevance
“…Because patients with chronic pancreatitis (CP) are at high risk for the development of DM, it is an important issue with significant implications for clinical practice. 2 de Miguel-Yanes et al 3 described a decreased rate of PEP and lower in-hospital mortality after endoscopic biliary sphincterotomy in people with type 2 DM in Spain, which is consistent with our study; the reduced incidence of PEP in CP patients was correlated with the prevalence of DM. 4 Despite the similar conclusion, we would like to point out 2 major differences: the included patients and the definition of DM.…”
Section: Responsesupporting
confidence: 92%
“…Because patients with chronic pancreatitis (CP) are at high risk for the development of DM, it is an important issue with significant implications for clinical practice. 2 de Miguel-Yanes et al 3 described a decreased rate of PEP and lower in-hospital mortality after endoscopic biliary sphincterotomy in people with type 2 DM in Spain, which is consistent with our study; the reduced incidence of PEP in CP patients was correlated with the prevalence of DM. 4 Despite the similar conclusion, we would like to point out 2 major differences: the included patients and the definition of DM.…”
Section: Responsesupporting
confidence: 92%
“…On the other hand, other studies found that the incidence of post-ERCP pancreatitis decreases in diabetic patients. This was explained by the presence of chronic pancreatitis and intrinsic gland fibrosis in diabetic patients which act as a protective factor against the development of pancreatitis [16,17]. On the other hand, we did not find any significant correlation between the development of post-ERCP pancreatitis and systemic hypertension among our patients, however, we found that systemic hypertension was higher in patients with post-ERCP pancreatitis.…”
Section: Discussioncontrasting
confidence: 75%